Analysis of Pilgrims' Perception of the Quality of South Sumatra Hajj Dormitory Services In the Implementation of Hajj in 2024 - Sholahuddin Sholahuddin; Intan Fuji Lestari (International Journal of Community Service & Engagement, 2025)
This study aims to analyze the perception of pilgrims on the quality of services provided by the South Sumatra Hajj Dormitory during the process of organizing the 2024 Hajj. Using a qualitative approach with the SERVQUAL (Tangibles, Reliability, Responsiveness, Assurance, and Empathy) analysis model, this study explores the experience, expectations, and evaluation of services based on empirical data from in-depth interviews and the results of pilgrim satisfaction surveys. The findings show that in general, the perception of pilgrims towards the aspects of Tangibles and Assurance is in the very good category, while in the dimensions of Empathy and Responsiveness, there is a disparity between expectations and the reality of service, especially in the early and elderly groups. Segmentation analysis based on group, age, and gender showed that there were variations in perceptions influenced by socio-cultural backgrounds, previous Hajj experiences, and physical conditions of pilgrims. The results of this study provide theoretical contributions in strengthening the SERVQUAL model in the context of religious services, as well as practical implications for improving public service governance based on congregational satisfaction in the future.